PENGARUH TINGKAT PENDIDIKAN DAN TURNOVER INTENTION TERHADAP KINERJA KARYAWAN PADA PT. TESO INDAH RANTAU BAKUNG KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Fikri, Khusnul; Utami, Sabrina (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research was conducted at PT. Teso Indah Rantau Bakung, Rengat Barat, Indragiri Hulu. This employee performance is not optimal and maximal because the factors that can influence it are coupled with the difference (gap) from the results of previous research, this becomes the rationale reason for the authors to conduct research. The purpose of this study is to determine and analyze the influence of the level of education and turnover intention on employee performance. This study used 90 people as sample. Data collection techniques in this study are: questionnaire, interview and document recording, then the data will analyzed by using Factor Analysis with Smart PLS 3. The results of this study indicate: (1) influential education level (2) Turrnover intention has a positive and significant effect on employee performance, (3) The level of education and tuning intention has a strong relationship with employee performance, (4) Employee performance is influenced by the level of education and turnover intention is 41 , 2%, the remaining 58.8% is explained by other independent variables not examined in this study